Giving Advice and Responding to it in a Spanish Discussion among Puerto Ricans - Angela Pinilla-Herrera (Journal of English Language Teaching and Linguistics, 2018)
Although advice is considered in many languages as a face-threatening speech act; in Spanish it is often seen as a solidarity-building tool that shows closeness among the interlocutors.  This study analyzes the advice sequences in a conversation between a Puerto Rican couple in order to identify the strategies, types of sentences, and reactions that took place during the verbal exchange.  Results show evidence that -contrary to building solidarity among Spanish speakers- advice can also serve as a tool for questioning, criticizing, and demeaning the interlocutor.